Pedagogical potentialities of lesson study for the reconstruction of teachers' dispositions. Issue 1 (3rd January 2017) - Peña Trapero, Noemi; Pérez Gómez, Ángel I.
Abstract : Purpose: The purpose of this paper is to show the relationship between lesson study (LS) and the reconstruction of teacher dispositions (practical knowledge). Design/methodology/approach: This work consists of an exhaustive qualitative study, analysis and interpretation of the practical knowledge of an infant school teacher before and after her participation in a training process based on LS. Findings: This work offers a response to this resistance to change and to progress in education. It demonstrates the potentiality of LS for the transformation of schools in the twenty-first century and the construction of a reflected, shared, emerging pedagogical capital for teachers. Originality/value: The analysis focusses on practical knowledge (knowledge-in-action, (Schön, 1998); implicit theories (Pozo, 2006; Marrero, 2009); phronesis (Kinsella and Pitman, 2012); tacit knowledge (Contreras and Pérez de Lara, 2010)) because in accordance with the latest theories deriving from cognitive neuroscience, most of the resources the authors use in their action come from unconscious mechanisms. Hence, the procedures and mechanisms of qualitative research have been used to carry out in-depth analysis through prolonged daily observation of practice under a series of previously established dimensions (knowledge, skills, attitudes, values and emotions).